Delamanid, Bedaquiline, and Linezolid Minimum Inhibitory Concentration Distributions and Resistance-related Gene Mutations in Multidrug-resistant and Extensively Drug-resistant Tuberculosis in Korea - Yang, Jeong Seong; Kim, Kyung Jong; Choi, Hongjo; Lee, Seung Heon (Annals of laboratory medicine, 2018)
Delamanid, bedaquiline, and linezolid have recently been approved for the treatment of multidrug- and extensively drug-resistant (MDR and XDR, respectively) tuberculosis (TB). To use these drugs effectively, drug susceptibility tests, including rapid molecular techniques, are required for accurate diagnosis and treatment. Furthermore, mutation analyses are needed to assess the potential for resistance. We evaluated the minimum inhibitory concentrations (MICs) of these three anti-TB drugs for Korean MDR and XDR clinical strains and mutations in genes related to resistance to these drugs. MICs were determined for delamanid, bedaquiline, and linezolid using a microdilution method. The PCR products of drug resistance-related genes from 420 clinical Mycobacterium tuberculosis strains were sequenced and aligned to those of M. tuberculosis H37Rv. The overall MICs for delamanid, bedaquiline, and linezolid ranged from ≤0.025 to >1.6 mg/L, ≤0.0312 to >4 mg/L, and ≤0.125 to 1 mg/L, respectively. Numerous mutations were found in drug-susceptible and -resistant strains. We did not detect specific mutations associated with resistance to bedaquiline and linezolid. However, the Gly81Ser and Gly81Asp mutations were associated with resistance to delamanid. We determined the MICs of three anti-TB drugs for Korean MDR and XDR strains and identified various mutations in resistance-related genes. Further studies are needed to determine the genetic mechanisms underlying resistance to these drugs.